The ω‐3 fatty acid α‐linolenic acid extends Caenorhabditis elegans lifespan via NHR‐49/PPARα and oxidation to oxylipins. Issue 5 (3rd August 2017) - Qi, Wenbo; Gutierrez, Gloria E.; Gao, Xiaoli; Dixon, Hong; McDonough, Joe A.; Marini, Ann M.; Fisher, Alfred L.
Summary: The dietary intake of ω‐3 polyunsaturated fatty acids has been linked to a reduction in the incidence of aging‐associated disease including cardiovascular disease and stroke. Additionally, long‐lived Caenorhabditis elegans glp‐1 germ line‐less mutant animals show a number of changes in lipid metabolism including the increased production of the ω‐3 fatty acid, α‐linolenic acid (ALA). Here, we show that the treatment of C. elegans with ALA produces a dose‐dependent increase in lifespan. The increased longevity of the glp‐1 mutant animals is known to be dependent on both the NHR‐49/PPARα and SKN‐1/Nrf2 transcription factors, although the mechanisms involved are incompletely understood. We find that ALA treatment increased the lifespan of wild‐type worms and that these effects required both of these transcription factors. Specifically, NHR‐49 was activated by ALA to promote the expression of genes involved in the β‐oxidation of lipids, whereas SKN‐1 is not directly activated by ALA, but instead, the exposure of ALA to air results in the oxidation of ALA to a group of compounds termed oxylipins. At least one of the oxylipins activates SKN‐1 and enhances the increased longevity resulting from ALA treatment. The results show that ω‐3 fatty acids inhibit aging and that these effects could reflect the combined effects of the ω‐3 fatty acid and the oxylipin metabolites. The benefits of ω‐3 fatty acid consumption on human health may similarly involve the production of oxylipins, and differences in oxylipin conversion could account for at least part of the variability found between observational vs. interventional clinical trials.